Controversies in the diagnosis and management of early gastric cancer - Bu, Zhaode; Ji, Jiafu (Chinese Journal of Cancer Research, 2013)
Early diagnosis and treatment is the key to improving the prognosis of gastric cancer. The past decades have witnessed the rapid advances in the diagnosis and management of early gastric cancer (EGC): endoscopy has played an increasingly important role, whereas laparoscopic techniques have also been introduced for EGC treatment. In China, the proportion of EGC is gradually increasing, and this condition will soon become a hot research topic. In this article, we will elucidate some major controversies in the diagnosis and management of EGC.